2014
DOI: 10.1097/phm.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Modalities and Rehabilitation Techniques in the Management of Neuropathic Pain

Abstract: Neuropathic pain is an important problem because of its complex natural history, unclear etiology, and poor response to standard physical therapy agents. It causes severe disability unrelated to its etiology. The primary goals of the management of neuropathic pain are to detect the underlying cause, to define the differential diagnosis and eliminate risk factors, and to reduce the pain. The physician should also know the functional and psychologic conditions of the patient. Therefore, a multimodal management p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 32 publications
0
53
0
5
Order By: Relevance
“…As pain is a complex symptom, in which not only physical factors but also psychological, neurophysiological, socioeconomic, and cultural aspects may influence the experience and continuation of pain, a multidisciplinary approach in line with the biopsychosocial model is required in optimizing treatment for the individual patient . Physical therapy modalities and rehabilitation techniques are important options . Moreover, supervised exercise in patients with metabolic syndrome showed an increased cutaneous regenerative capacity, suggesting potential benefits of peripheral nerve function …”
Section: Epidemiologymentioning
confidence: 99%
“…As pain is a complex symptom, in which not only physical factors but also psychological, neurophysiological, socioeconomic, and cultural aspects may influence the experience and continuation of pain, a multidisciplinary approach in line with the biopsychosocial model is required in optimizing treatment for the individual patient . Physical therapy modalities and rehabilitation techniques are important options . Moreover, supervised exercise in patients with metabolic syndrome showed an increased cutaneous regenerative capacity, suggesting potential benefits of peripheral nerve function …”
Section: Epidemiologymentioning
confidence: 99%
“…However, it is highly unlikely that the effect of a single acute infusion of steroids lasted for all of the 12-month follow-up period. We hypothesize that the early (1-2 month) effect of the blocking procedure positively influenced other aspects of pain and its treatment, such as the efficacy of physical therapy [2], reduced use of medication and positive effects on mood, that as a whole, provided long-term positive effects. In fact, our results suggest that the positive effect of the treatment built up during the early study phase and persisted for 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Electrotherapy has been described as physical therapy method with potential analgesic effect on NP, especially diabetic neuropathic pain. Studies have shown transcutaneous electrical nerve stimulation (TENS) as preferential method 21 . In a meta-analysis 22 , TENS to treat diabetic neuropathy had medium-term beneficial effects (6 and 12 weeks) in pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that TENS activates analgesia-producing central mechanisms. There are evidences that low frequency TENS activates µ opioids in spinal cord and brainstem, and high frequency currents would produce effect by means of δ receptors 21 . Mima et al 23 have observed that high frequency TENS also decreases motor evoked potential amplitude, suggesting a decrease in corticospinal and motor cortex excitability.…”
Section: Introductionmentioning
confidence: 99%